2009
DOI: 10.1080/13506280902916691
|View full text |Cite
|
Sign up to set email alerts
|

Do we look at lights? Using mixture modelling to distinguish between low- and high-level factors in natural image viewing

Abstract: The allocation of overt visual attention while viewing photographs of natural scenes is commonly thought to involve both bottom-up feature cues, such as luminance contrast, and top-down factors such as behavioural relevance and scene understanding. Profiting from the fact that light sources are highly visible but uninformative in visual scenes, we develop a mixture model approach that estimates the relative contribution of various low and high-level factors to patterns of eye movements whilst viewing natural s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 44 publications
3
54
0
Order By: Relevance
“…The probabilistic framework we use in this paper (10,19) is easily extended to study spatiotemporal effects, by modeling the conditional probability of a fixation given previous fixations (Materials and Methods and ref. 12).…”
Section: Discussionmentioning
confidence: 99%
“…The probabilistic framework we use in this paper (10,19) is easily extended to study spatiotemporal effects, by modeling the conditional probability of a fixation given previous fixations (Materials and Methods and ref. 12).…”
Section: Discussionmentioning
confidence: 99%
“…As visual features such as luminance, contrast, and edge density in scenes have been shown to correlate with the rated semantic informativeness of a location [8], gaze may be guided toward an object due to its cognitive relevance, and the corresponding peak in feature values around foveation may simply be a by-product of this correlation. For example, a recent study by Vincent et al [108] used mixture modeling to isolate the independent contributions of low and high-level visual features to fixations in static scenes. The authors found that low-level features in isolation contributed very little to fixation location compared to the much larger contribution of central bias and preference for foreground objects.…”
Section: Bottom-up Versus Top-down Control During Ongoing Dynamic Scenesmentioning
confidence: 99%
“…They include both bottom-up and top-down factors. This approach was first proposed by Vincent et al [32] and later by Couronné et al [33]. In Vincent's study, the a priori top-down guiding factors are set up according to the semantic of the scenes.…”
Section: Statistical Modelmentioning
confidence: 99%